Literature Review: Teknik Menurunkan Intensitas Nyeri pada Ibu Bersalin - Herawaty Herawaty; Ni Wayan Armini; Ni Gusti Ayu Kompyang Sriasih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Labor pain is a type of labor pain that varies in intensity depending on the person. This pain is frequently regarded by the mother as the most severe pain she has ever felt. The goal of this study is to study into some related literature to minimize the intensity of labor searching. The strategy used in this study was metadata analysis combined with a literature evaluation to lower labor pain intensity. There are 14 research publications that are in accordance with this research, based on various studies that have been conducted. Based on the findings, it has been shown that non-pharmacological treatment can reduced the intensity of discomfort experienced by laboring mothers more convenient to do either health workers or patient companions is Birth Ball technique, massaging the lower back and taking deep breaths during contractions. The findings of this study can be utilized as a guide when offering non-pharmacological treatment to mothers who are experiencing severe labor pain.